Ablation of BATF Alleviates Transplant Rejection via Abrogating the Effector Differentiation and Memory Responses of CD8+ T Cells - Li, Shuang; Zou, Dawei; Chen, Wenhao; Cheng, Yating; Britz, Gavin W.; Weng, Yi-Lan; Liu, Zhaoqian (Frontiers in Immunology, 2022)
Allogeneic CD8+ T cells are prominently involved in allograft rejection, but how their effector differentiation and function are regulated at a transcriptional level is not fully understood. Herein, we identified the basic leucine zipper ATF-like transcription factor (BATF) as a key transcription factor that drives the effector program of allogeneic CD8+ T cells. We found that BATF is highly expressed in graft-infiltrating CD8+ T cells, and its ablation in CD8+ T cells significantly prolonged skin allograft survival in a fully MHC-mismatched transplantation model. To investigate how BATF dictates allogeneic CD8+ T cell response, BATF–/– and wild-type (WT) CD8+ T cells were mixed in a 1:1 ratio and adoptively transferred into B6.Rag1–/– mice one day prior to skin transplantation. Compared with WT CD8+ T cells at the peak of the rejection response, BATF–/– CD8+ T cells displayed a dysfunctional phenotype, evident by their failure to differentiate into CD127–KLRG1+ terminal effectors, impaired proliferative capacity and production of pro-inflammatory cytokines/cytotoxic molecules, and diminished capacity to infiltrate allografts. In association with the failure of effector differentiation, BATF–/– CD8+ T cells largely retained TCF1 expression and expressed significantly low levels of T-bet, TOX, and Ki67. At the memory phase, BATF-deficient CD8+ T cells displayed impaired memory responses upon allogeneic antigen re-stimulation. Therefore, BATF is a critical transcriptional determinant that governs the terminal differentiation and memory responses of allogeneic CD8+ T cells in the transplantation setting. Targeting BATF in CD8+ T cells may be an attractive therapeutic approach to promote transplant acceptance.